Distance Learning and School-Related Stress Among Belgian Adolescents During the COVID-19 Pandemic - De Coninck, David; Matthijs, Koen; Van Lancker, Wim (Frontiers in Education, 2022)
To improve our understanding of the mental health consequences of the shift to distance learning during the COVID-19 pandemic, this study examined which factors are associated with increased school-related stress in adolescents. The sample consists of 16,093 adolescents, aged 12 to 18, who were enrolled in secondary education in Flanders, Belgium in May 2020. Stepwise binomial logistic regressions were used to investigate associations between the (online) learning environment, family-, and peer-related factors and increased stress in adolescents, controlling for sociodemographic characteristics. Results show that overcrowding, financial difficulties, and domestic violence are risk factors for increased stress, while social support and no material deprivation are protective factors. These findings suggest that, in addition to distributing the necessary materials for distance learning, also social policy efforts are required to compensate for the negative effects of distance learning. Without this, distance learning may fail to deliver equal educational opportunities and outcomes.